IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE PADA PERBANKAN SYARIâAH DI INDONESIA - Setyani, Nur Hidayati (Economica: Jurnal Ekonomi Islam, 2012)
Bank is financial institution, which is a fungtioning financial intermediary from two parties, namely sides that excess fund and poor one party lents fund. Principle syariâah is ruling indentured base islamic law among bank and party othering to keep fund and/or business activity finanance, or stated another activity according to syariâah.Good corporate governance (GCG) is manner brings of bank that are principles apply; transparency , accountability, responsibility, independency and fairness. GCGâs principles really back up syarâi. In Islam also recognized many muamalahâs principles as; justice, tazawun, masuliyah, behaviour, shiddiq, trust ,fathanah , tabligh hurriyah, charity, wasathan, ghirah, idarah, khalifah, aqidah , ijabiyah, raqabah, qiraâah and islah. ImplementationÂ  about performing GCG at various institute carries on business to get profitâs orientation, notably financial institution/syariâah bank, constitute a certainty, even syariâahâs financial institutions in particular bank syariâah, ought to becomes pionir, since to carried on terminological islamic principles.